The Effect of Social Media Use Frequency on Adolescent Mental Health at Man 3 Tangerang - Lia Mulyanti; Devi Intan Sari; Fitriani Nur Damayanti; Siti Nurjanah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Social media has many positive influences that we can accept, but there are also many negative influences that occur due to social media, especially on mental health. Social media is present as part of the development of the internet. Its presence offers easy and new ways to interact, communicate, and socialize with the support of interesting features. The number of social media users in Indonesia is dominated by teenagers, so the impact is felt most by teenagers. Good use can improve achievement, conversely, bad use can have negative consequences for children and teenagers. Purpose: This study was to determine the effect of the frequency of social media use on the mental health of teenagers at MAN 3 Tangerang. Results: The level of social media use was high for 144 respondents (53.5%), and the mental health of teenagers was good for 137 respondents (50.9%). Conclusion: There is an influence of social media on mental health in teenagers at MAN 3 Tangerang.